KEMAMPUAN BERPIKIR KREATIF DITINJAU DARI GAYA BELAJAR DALAM MATERI SEGI EMPAT DI SMP - Eva Satriani; Yulis Jamiah; Ahmad Yani T (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstrakThe purpose of this study to describe how mathematics creative thinking abilities of students in the rectangular material in the students' learning styles in SMP Negeri 3 Pontianak. Aspects want clarified, namely: mathematics creative thinking abilities of students studying learning styles are visual, auditory and kinesthetic. The method used is descriptive method in the form of case study research. Subjects were students of class VIII A SMP Negeri 3 Pontianak. Based on the results obtained show that the mathematical creative thinking abilities of students with visual learning styles in class VIII SMP Negeri 3 Pontianak to meet all four indicators of the ability to think creatively mathematically, ie smooth, flexibility, originality, and elaboration. mathematical creative thinking abilities of students with auditory learning styles in class VIII SMP Negeri 3 Pontianak to meet two of the four indicators of the ability of creative thinking mathematically, that is smooth, and flexibility. Mathematical and creative thinking abilities of students with kinesthetic learning styles in class VIII SMP Negeri 3 Pontianak to meet two of the four indicators of the ability of creative thinking mathematically, that is smooth, and elaboration.Keywords: Learning Style, Mathematical Creative Thinking ,  Rectangular